'An object lesson in how not to get things done': Edinburgh's Unbuilt 'Opera House', 1960–75. Issue 1 (November 2017) - Fair, Alistair
Abstract : This article examines the proposals of 1960–75 for a major new theatre in central Edinburgh. Popularly known as the 'opera house', the proposed Castle Terrace Theatre (which was never built) was a regular feature in the local press, with frequent reports of delays, funding crises, architectural debate and concerns about the designs themselves. It is argued here that the real issue, however, was that, despite claims of an expansive cultural policy, central government funding for such major projects as the 'opera house' was less forthcoming than was the case for the many smaller theatres that were successfully built across Britain during this period.